Analyzing Mathematics Education Students' Misconceptions on Limit Functions : A Case Study at Alkhairaat University - Hajerina, Hajerina; Rochaminah, Sutji; Suciati, Indah (Jurnal Pendidikan MIPA, 2025)
Abstract: The purpose of this study was to determine the misconceptions made by Unisa Mathematics Education students about the concept of limit.  The research method used was a descriptive qualitative approach or survey design, where data were collected through comprehension tests, interviews, and observations of 16 students. The results showed that students consider limit as something that is not reached, limit is an estimate, limit is a boundary, and a function will always have a limit at a certain point. Other misconceptions are that students consider limit as a substitution process, even though the substitution process causes the denominator to become 0, students still write 0, and they think that when the function has a limit value, the function is defined at a certain point and must be continuous. These findings are expected to contribute to the development of more effective learning strategies to overcome misconception in Mathematics Education students and improve their understanding of calculus concepts, especially function limit.       Keywords: limit concept, limits of functions, misconceptions.